Positive solutions for nonlinear Schrödinger–Kirchhoff equations in R3. (June 2020) - Chen, Wei; Fu, Zunwei; Wu, Yue
Abstract: In this paper, we study the nonlinear Schrödinger–Kirchhoff-type equation with pure power nonlinearities in R 3 by variational methods. By carrying out the constrained minimization on a special manifold which is a combination of the Nehari manifold and Pohozaev manifold, we proved the existence of positive radial solutions of this equation for the power p ∈ ( 1, 5 ) . The results of this paper extend some existing conclusions, especially for p ∈ ( 1, 2 ] .